The potential for freshwater citizen science to engage and empower: a case study of the Rivers Trusts, United Kingdom - Collins, Rob; France, Anneka; Walker, Michelle; Browning, Simon (Frontiers in Environmental Science, 2023)
Rivers Trusts in the UK work to protect and restore freshwater ecosystems. This includes the provision of citizen science opportunities that encompass water quality monitoring, assessment of polluting outfalls, surveying riverine plastic pollution, mapping and control of freshwater invasive species and assessment of the biological health of rivers. In some cases, citizen science data has led directly to action being taken to address a pollution source and, in one example, indirectly influenced policy focus. Online platforms play an increasingly important role in capturing and portraying citizen science data. A large multi-stakeholder initiative aims to achieve a step-change in the contribution of citizen science to the assessment of river health including development of a standardised national framework. There is potential for citizen science to widen the monitoring of freshwater to encompass toxic chemicals.